2019
DOI: 10.1177/1056492618817827
|View full text |Cite
|
Sign up to set email alerts
|

Playing the Game: Unpacking the Rationale for Organizational Corruption in MNCs

Abstract: What conditions must be present for multinational companies (MNCs) to benefit from corruption? We argue that corrupt acts by organizations can be profitable if four conditions are met: there must be an opportunity to do so, the risks must be perceived as low, the organization must be willing to engage in corruption, and it must have some skill in converting such acts into organizational advantages. We believe all of these conditions are necessary for organizational corruption to “pay off.” We argue that these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 69 publications
(106 reference statements)
1
15
1
Order By: Relevance
“…However, when such approaches fail and community relations break down, firms may need to bargain with formal and informal community leaders (Haslam & Tanimoune, 2016). For instance, corporate managers may resort to paying bribes to local officials (Zyglidopoulos, Dieleman, & Hirsch, 2019), or offer local investments in public good services-e.g., hospitals, infrastructure, religious facilities, or sports centres (Elg et al, 2015)-as bargaining tools aimed at improving community relations that may represent better alternatives to paying bribes.…”
Section: Managing Risk In Emerging Marketsmentioning
confidence: 99%
“…However, when such approaches fail and community relations break down, firms may need to bargain with formal and informal community leaders (Haslam & Tanimoune, 2016). For instance, corporate managers may resort to paying bribes to local officials (Zyglidopoulos, Dieleman, & Hirsch, 2019), or offer local investments in public good services-e.g., hospitals, infrastructure, religious facilities, or sports centres (Elg et al, 2015)-as bargaining tools aimed at improving community relations that may represent better alternatives to paying bribes.…”
Section: Managing Risk In Emerging Marketsmentioning
confidence: 99%
“…in CSI outweigh the risks (Hirsch and Milner, 2016), which means that MNEs may be insufficiently motivated to consistently reinforce policy requirements. Given the many practical examples of persistent CSI behaviors, ranging from mining controversies to poor employee practices, child labor and consumer harm, it is apparent that, despite the adoption of stringent laws and financial penalties to curtail CSI, MNEs may expect no penalties and even positive returns from CSI (Cuervo-Cazurra and Genc, 2006;Cuervo-Cazurra, 2016;Zyglidopoulos et al, 2020). Some studies have already pointed to the limitations with formal regulatory mechanisms designed to motivate MNEs to behave responsibly (Hill et al, 2019;Wälde, 2002).…”
Section: Complexity Of International Businessmentioning
confidence: 99%
“…Furthermore, evidence on the association between CSI, reputation and social regulation remains mixed. Some studies report a significant decline in reputation-based firm specific advantage (FSA) following CSI (Karpoff et al, 2005;Karpoff et al, 2008;Zyglidopoulos et al, 2020), whereas others illustrate a nuanced process of reputation erosion, dependent on the type of firm associated with CSI (Karpoff et al, 2005). Recently, Nardella et al (2020) found that, overall, CSI does not have a significantly negative impact on firm reputation and that the social regulation process was only enacted after being found culpable by a court of law.…”
Section: Complexity Of International Businessmentioning
confidence: 99%
“…Conversely, "continuous risks" -e.g. corruption -may be less country-specific and capabilities developed to deal with such risks in one country can be expected to be valuable to deal with similar risks in other countries (Oh & Oetzel, 2017: 727;Perkins, 2014;Qi et al, 2018;Zyglidopoulos et al, 2019).…”
Section: The Transferability Of Political Capabilitiesmentioning
confidence: 99%